The Role of Microfinance Institutions in Supporting Financial Inclusion and Economic Empowerment in Indonesia - Adiguna, Patria; Kusnaedi, Ujang; Hakim, Rahman (Jurnal Ilmiah Akuntansi & Bisnis, 2024)
This research aims to examine the role of Microfinance Institutions (MFIs) in supporting financial inclusion and community economic empowerment, especially for the poor and micro-entrepreneurs in Indonesia. Using a normative juridical approach, this research analyzes the regulations and operations of MFIs based on Law No. 1 Year 2013 on MFIs as well as secondary data from literature and interviews with relevant practitioners. The research was conducted for three months, from June to August 2024, focusing on MFI regulations, operations, and challenges in Indonesia. Data were collected through literature study, legal document analysis, and in-depth interviews with 20 respondents located in the West Jakarta area, including MFI managers, micro business actors, and academics. The results show that MFIs play an important role in providing microfinance, savings, and business advisory services that support economic empowerment and community welfare improvement. However, regulation implementation still faces challenges, including policy harmonization between central and local governments, limited capital, and low financial literacy of customers. In addition, competition with modern financial institutions is also an obstacle to the sustainability of MFIs. This study recommends strengthening regulations, harmonizing policies, and increasing the operational capacity of MFIs through technical support, training, and capital incentives. Financial literacy also needs to be improved so that people can optimally utilize microfinance services. Thus, MFIs can be a more effective instrument in supporting sustainable economic development and financial inclusion in Indonesia.